Cytokinin induces bacterial pathogen resistance in tomato. (30th September 2020) - Gupta, Rupali; Leibman‐Markus, Meirav; Pizarro, Lorena; Bar, Maya
Abstract: Phytohormones are involved in the regulation of plant responses to biotic stress. How a limited number of hormones differentially regulate defence responses and influence the outcome of plant–biotic interactions is not fully understood. In recent years, cytokinin (CK) was shown to induce plant resistance against several pathogens. In the present study, we investigated the effect of CK in inducing tomato resistance against the hemibiotrophic pathogenic bacteria Xanthomonas campestris pv. vesicatoria (Xcv) and Pseudomonas syringae pv. tomato (Pst). We demonstrate that CK enhances tomato resistance to Xcv and Pst through a process that relies on salicylic acid and ethylene signalling. CK did not directly affect the growth or biofilm formation ability of these pathogens in vitro. Overall, our work provides insight into the underlying mechanisms of CK‐induced immune responses against bacterial pathogens in tomato. Abstract : Cytokinin promotes bacterial pathogen resistance in tomato in a salicylic acid‐ and ethylene‐dependent mechanism.